Study the ICT-Based Tutorial Model for Upper-Class of Elementary School in the Perspective of Constructivist Approach - Chasanah, Uswatun; Prastowo, Andi (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
This research aims to reveal the syntax, factors that take effect the application process of the ICT-based tutorial model, and the strengths of the tutorial model from a constructivist approach to online learning. The research method used in this research is the library research method with a descriptive qualitative approach. The research subjects were online learning articles and tutorial models. The data analysis technique was carried out by analyzing the contents of the document, namely precious research scientific articles and relevant theories. The results in this study point out that the tutorial model can be one of the solutions and means to be utilized during the online learning process SD/MI. the tutorial model was developed by combining the software in a coherent and tested manner. Variations of tutorial models are tailored to the needs and characteristics of students. The syntax of the ICT-based tutorial model includes an introduction, presentation of information, question and responses, judging of responses, providing about responses,Â  remediation, sequencing lesson segment, and closing. The ability of teachers and students, as well as the existence of devices, laptops, and internet networks, are supporting factors. Meanwhile, the quality of the internet network connection speed is an inhibiting factor. The tutorial model can facilitate students to be more independent when learning, evaluate self-achievement, flexible, and learner-centred. However, the tutorial model can trigger boredom, frustration due to frequent remedies, depending on teacher directions, and limited free applications. The tutorial model is in tune with the perspective of a constructivist approach. The ICT-based tutorial model can help teachers carry out online learning according to process standards, provide meaningful experiences for students, effective, and efficient experiences for students.